2021
DOI: 10.1002/ente.202100190
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Sodium Salt Electrolyte Compatible with Na0.67Ni0.15Fe0.2Mn0.65O2 Cathode for Sodium‐Ion Batteries

Abstract: The construction of an optimized electrolyte system compatible with layered transition metal (TM) oxides is of great importance to advanced sodium‐ion batteries (SIBs). Herein, a low‐cost iron‐containing manganese‐based layered cathode material of Na0.67Ni0.15Fe0.2Mn0.65O2 (N‐NFM) is prepared through an improved coprecipitation method. Then, the chemical properties of interfaces between the N‐NFM cathode and organic liquid electrolytes based on NaClO4 and NaPF6 are investigated, respectively. Results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The peak around 781 (002 plane) is significantly enhanced after 100 cycles for both samples, representing a characteristic peak of AI. 29 The XRD characterizations concluded that the cathode material structure is more stable for the doped titanium sample (NNM-Ti0.02) than the NNM sample. Fig.…”
Section: Battery Cathodes After Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak around 781 (002 plane) is significantly enhanced after 100 cycles for both samples, representing a characteristic peak of AI. 29 The XRD characterizations concluded that the cathode material structure is more stable for the doped titanium sample (NNM-Ti0.02) than the NNM sample. Fig.…”
Section: Battery Cathodes After Cyclingmentioning
confidence: 99%
“…It demonstrated that doping the titanium can be conducive to the migration of Na + . 29 In order to verify the contribution of titanium doping to the capacity of the batteries, a cyclic voltammetry test was performed. The peak area of NNM-Ti0.02 was the largest, which indicates that the material contributed the most capacity among other batteries under similar conditions.…”
Section: Electrochemical Performance Of Batteriesmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) disclosed the existence of a CEI on the NVPF surface (Figure S11, Supporting Information). This included prospective inorganic components such as fluoride and fluorophosphate derived from [PF 6 ] − , as well as organic compounds comprising C-C/C-H, C-O, C=O, and C-N. [8,50] It is crucial to mention that the sole source of N-containing constituents is [DEME] + , which underscores the advantageous nature of the IL. However, no associated component was evident on the BASE's surface, signifying that a redox reaction regarding passivation layer formation did not take place on it.…”
Section: Cell Performancementioning
confidence: 99%
“…This resulted in more organic compounds and fewer inorganic compounds, with a decrease in the stability of the CEI. [87] Local high-concentration electrolytes have been extensively studied for lithium-ion batteries. [111,112] By contrast, relatively little research has been conducted on using local high-concentration electrolytes in sodium-ion batteries.…”
Section: Cei On the Surface Of Transition Metal Oxide Cathode Materialsmentioning
confidence: 99%
“…The NaPF 6 ‐based electrolyte was found to be more compatible with the cathode material, facilitating Na + transference. [ 87 ] A study by Ma et al showed that PC/EMC served as an optimized electrolyte formula. When combined with various additives, this optimized electrolyte could inhibit the chemical dissolution of transition metal ions in dehydrogenated (charged) NFM.…”
Section: Cathode Materials and Electrolytes For Sodium‐ion Batteriesmentioning
confidence: 99%